2022
DOI: 10.1021/acssuschemeng.2c02360
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Copper Catalysts for the Fluidized Electrocatalytic Hydrogenation of Furfural to Furfuryl Alcohol

Abstract: Electrocatalytic hydrogenation is an efficient and environmentally friendly way to convert biomass derivatives into high-value-added chemicals and biofuels, although in most cases, the Faraday efficiency (FE) is low. Herein, Cu electrocatalysts with a bicontinuous nanoporous structure and high specific surface area were fabricated by chemical dealloying of CuAl alloy. For the electrocatalytic hydrogenation of furfural to furfuryl alcohol, as a biomass-derived platform molecule reaction, the nanoporous Cu (NP-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Prior reports confirmed that, similar to furfural that can only undergo aldehyde hydrogenolysis to produce 2-methylfuran under acidic conditions, , HMF hydrogenolysis for DMF formation is facilitated in acidic electrolytes only, Figure . Zhang et al report electrodeposited Ni onto a high-surface Cu-electrode to conduct HRR in a 0.2 M sulfate buffer solution (pH 2.0) that exhibited a high Faradaic efficiency (FE) of 88%) and DMF selectivity of 88.9% .…”
Section: Principle Of Hrrmentioning
confidence: 81%
“…Prior reports confirmed that, similar to furfural that can only undergo aldehyde hydrogenolysis to produce 2-methylfuran under acidic conditions, , HMF hydrogenolysis for DMF formation is facilitated in acidic electrolytes only, Figure . Zhang et al report electrodeposited Ni onto a high-surface Cu-electrode to conduct HRR in a 0.2 M sulfate buffer solution (pH 2.0) that exhibited a high Faradaic efficiency (FE) of 88%) and DMF selectivity of 88.9% .…”
Section: Principle Of Hrrmentioning
confidence: 81%
“…Therefore, it was applied for the anodic HMF reaction, referring with a very promising activity. In electrochemical applications, conventional catalysts for reducing NP to AP are usually synthesized at high pressures or temperatures, whereas Ni and compounds of Ni are potential alternatives to conventional noble metal catalysts, being cheaper and easier to handle, and can be obtained under mild conditions. A layered CuNi-Cu 2 O/NiAlO x nanocatalyst synthesized by Fu et al was able to reduce NP to AP at a concentration of 20 g L –1 in 20 min, and the conversion efficiency and selectivity of NP to AP could also exceed 99.99% after 27 cycles …”
Section: Introductionmentioning
confidence: 99%
“…Ding and co-workers proposed the chemical dealloying of CuAl alloys to fabricate nanoporous Cu electrocatalysts (NP-Cu 2 ) with a bicontinuous nanoporous structure and high roughness. 60 The NP-Cu 2 achieved remarkable selectivity (96%) and high FE (95%) of FAL in fluidized electrocatalysis, surpassing commercial Cu sheets and Cu nanocatalysts, which means that moderate roughness and specific surface area on bulky Cu can afford sufficient *H for ECH and inhibit DER. In general, poorly coordinated surface sites and defects formed by the roughening procedure tend to increase active site density and boost ECH activity.…”
Section: Electrochemical Hydrogenation Of Furansmentioning
confidence: 97%